1989
DOI: 10.1002/lsm.1900090406
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of the application of the Er:YAG laser on dental hard substances: II. Light microscopic and SEM investigations

Abstract: Many studies have been undertaken trying to use various laser systems as optical drills on dental enamel and dentin, but the high radiant exposure needed and subsequent high temperature rises lead to fractures of the hard substances and possible damages to the pulp. Compared to the other laser systems, the use of the Er:Yag laser has given encouraging results. Optical and scanning electron microscopy showed only minimal if any damage of the surrounding tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
272
1
11

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 438 publications
(287 citation statements)
references
References 18 publications
3
272
1
11
Order By: Relevance
“…In the current study, the irradiation of the Er:YAG laser at energy density of 80.19J/ cm 2 created a mean increase in temperature of 0.74 o C. The reduced increase of temperature is in agree ment with the findings of 10 who verified that the majority of the incident energy is consumed in the ablative process and only a small frac tion of the energy results in heating the remaining tissue, causing no damage. The reduction of temperature change is also obtained from the use of constant water cooling, in accordance with Attrill et al (2004), 16 who observed that the application of an Er:YAG laser without water cooling would exceed the temper ature increase threshold of 5.6ºC.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In the current study, the irradiation of the Er:YAG laser at energy density of 80.19J/ cm 2 created a mean increase in temperature of 0.74 o C. The reduced increase of temperature is in agree ment with the findings of 10 who verified that the majority of the incident energy is consumed in the ablative process and only a small frac tion of the energy results in heating the remaining tissue, causing no damage. The reduction of temperature change is also obtained from the use of constant water cooling, in accordance with Attrill et al (2004), 16 who observed that the application of an Er:YAG laser without water cooling would exceed the temper ature increase threshold of 5.6ºC.…”
Section: Discussionsupporting
confidence: 90%
“…Some Er:YAG laser beams could penetrate to deeper areas than the ablated area and damage the nerve fi bres and terminals, which might be a mecha nism of pain reduction in cavity ablation with the Er:YAG laser. 1 A number of authors 10,13,16,[18][19][20][21][22][23] stud ied the behaviour of different lasers to determine the amount of temperature increase during cavity preparation on dental structure. Keller et al (2003) 19 verified a mean temperature rise of 1.68ºC in the pulpal chamber using CO 2 and morphologically unaltered dentine surfaces, demonstrat ing the safe and tissue preserving char acter of the laser.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Previous reports have claimed that there are certain advantages in bonding to lased dentin because of an apparently enlarged surface area for adhesion based on the scaly and flaky surface appearance following Er:YAG irradiation. [33][34][35] In a study, the shear bond strength in deep lased dentin was better than in superficial lased dentin. 36 In addition, acid etching the previously laser-conditioned dentin surfaces has proved to be an effective technique.…”
Section: Discussionmentioning
confidence: 99%